Pengaruh Kualitas Pelayanan dan Fasilitas Kampus terhadap Kepuasan Mahasiswa di PIP Semarang - Mashudi Rofik; Ahmad Narto; Hilda Emeraldo Ahmad Adiarsa (Arbain Publishing, 2025)
The objective of this study is to analyse the relationship between service quality, facility quality, and student satisfaction at the Semarang Merchant Marine Polytechnic (PIP). This research is grounded in the significant contribution of service quality and the provision of adequate facilities in maritime education and training, which are essential for supporting the competence of cadets, student officers, and other learners, as well as for fostering their continued loyalty. The present study adopted a quantitative research design employing data collection through a survey, with data collected through a well-structured survey instrument questionnaire and analysed using linear regression. The study results indicate that the grade of educational provisions and infrastructure produces a favourable and statistically significant influence on student contentment. These findings suggest that simultaneous or partial improvements in the aspects of services and facilities can increase customers' positive perceptions of institutions. The results derived from this study offer practical implications for administrator at PIP Semarang in formulating strategies to enhance the management of services and facilities, thereby fostering customer satisfaction and sustaining loyalty.